Lithium adsorbent material, method of making and use thereof

The lithium adsorption material is prepared by bonding the polysulfonamide skeleton with the amino-modified lithium ion sieve, which solves the problems of acid and alkali resistance, hydrophilicity and selectivity of the lithium adsorption material in the high magnesium-lithium ratio sulfate salt lake, and realizes efficient lithium ion adsorption and separation.

CN119488888BActive Publication Date: 2025-10-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311049845.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-10-14
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

Existing lithium adsorption materials have poor acid and alkali resistance, poor hydrophilicity, low lithium adsorption capacity and poor selectivity in sulfate salt lakes with high magnesium-lithium ratios, making it difficult to effectively separate lithium ions.

Method used

The lithium adsorption material is prepared by chemically bonding a polysulfonamide skeleton and an amino-modified lithium ion sieve. The electrostatic interaction between the sulfonamide bond -SO2-NH- and Li+ is used to quickly capture lithium ions, and the selectivity is improved through the synergistic effect of amino crown ether.

Benefits of technology

The adsorption rate and lithium ion adsorption capacity of the lithium adsorption material are improved, the magnesium-lithium selectivity is enhanced, and the stability of the material structure is maintained under acidic and alkaline conditions. It is suitable for lithium ion extraction from sulfate salt lakes with high magnesium-lithium ratios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488888B_ABST
    Figure CN119488888B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of lithium ion adsorption material, and discloses a lithium adsorption material, a preparation method and application thereof.The lithium adsorption material comprises a polysulfonamide skeleton and an amino-modified lithium ion sieve bonded in the skeleton; the lithium ion sieve is connected with the skeleton through a structure shown in formula I; the polysulfonamide skeleton comprises structural unit A, structural unit B and structural unit C; the structural unit A and the structural unit C are connected through a structure shown in formula II; the structural unit B and the structural unit C are connected through a structure shown in formula III; Ar1 is the residue of a polyamine; Ar2 is the residue of a poly sulfuryl chloride; and Ar3 is the residue of an amino crown ether.The lithium adsorption material has high adsorption capacity, high magnesium-lithium selectivity and fast adsorption rate.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of lithium ion adsorption materials, in particular to a lithium adsorption material and a preparation method and application thereof. BACKGROUND

[0002] The methods for extracting lithium from domestic salt lakes mainly include adsorption, precipitation, extraction, electrodialysis and calcination, etc., among which the adsorption method has the advantages of simple process, green energy saving and good selectivity, and is superior to other methods in terms of time and cost, and has a broad application prospect. The adsorption method is the current mainstream process, and the core is the adsorbent. High magnesium-lithium ratio is a major feature of salt lakes in China. The separation of magnesium and lithium ions is difficult due to their similar chemical properties and similar hydration radii. In addition, the high sulfate radical in the sodium sulfate subtype salt lake has a higher requirement for the adsorbent. There is a binding action between SO4 2- and Li + , and they exist in the form of contact ion pair [Li2SO4(H2O) n ]0, and the diffusion rate of lithium ions is slow. Therefore, it is urgent to solve the adsorbent suitable for high magnesium-lithium ratio sulfate type salt lake. SUMMARY

[0003] The purpose of the present application is to overcome the problems of poor acid and alkali resistance, poor hydrophilicity, low lithium adsorption capacity and poor selectivity of the prior art lithium adsorption material, and to provide a lithium adsorption material and a preparation method and application thereof. The lithium adsorption material has a polysulfonamide skeleton, and the amino-modified lithium ion sieve is bonded in the skeleton by bonding, so that the lithium ion sieve is not easy to fall off from the skeleton.

[0004] The inventors found that in the sulfate type salt lake, SO4 2- has a binding action with Li + , and exists in the form of contact ion pair, that is, [Li2SO4(H2O) n ]0. The electrostatic interaction between the sulfonamide bond -SO2-NH- in the lithium adsorption material of the present application and Li + can quickly capture Li + near the adsorption site, destroy the first water and layer of the Li + hydration structure, and further destroy the electrostatic interaction between SO4 2- and Li + , so that Li + exists in the form of a bare ion, thereby making Li + quickly enter the internal pore of the ion sieve or the amino crown ether, so as to accelerate the adsorption reaction rate.

[0005] In order to achieve the above purpose, the present application provides a lithium adsorption material, wherein the lithium adsorption material comprises a polysulfonamide skeleton and an amino-modified lithium ion sieve bonded in the skeleton.

[0006] The lithium ion sieve is connected with the framework through a structure shown in formula I;

[0007]

[0008] The polysulfonamide framework comprises structural unit A, structural unit B and structural unit C;

[0009] The structural unit A and the structural unit C are connected through a structure shown in formula II;

[0010]

[0011] The structural unit B and the structural unit C are connected through a structure shown in formula III;

[0012]

[0013] Ar1 is a residue of a polyamine; Ar2 is a residue of a poly sulfuryl chloride; and Ar3 is a residue of an amino crown ether.

[0014] The second aspect of the present application provides a lithium adsorption material and a preparation method thereof, comprising the following steps:

[0015] (1) The lithium ion sieve is subjected to amination modification to obtain an amination-modified lithium ion sieve;

[0016] (2) The amination-modified lithium ion sieve, a polyamine and an amino crown ether are uniformly mixed in water to obtain a mixed solution 1;

[0017] (3) An organic solution containing a poly sulfuryl chloride is dropped into the mixed solution 1 under stirring to obtain a mixed solution 2 for reaction, and the product after reaction is subjected to heat treatment to obtain a semi-solid crosslinked product, and the lithium adsorption material is obtained after extrusion.

[0018] The third aspect of the present application provides a lithium adsorption material prepared by the above preparation method.

[0019] The fourth aspect of the present application provides an application of the above lithium adsorption material in lithium extraction from salt lakes.

[0020] Through the above technical solution, the lithium adsorption material and the preparation method and application thereof provided by the present application have the following beneficial effects.

[0021] The lithium adsorption material of the present application has a polysulfonamide framework comprising structural unit A, structural unit B and structural unit C, and the amination-modified lithium ion sieve is dispersed in the polymer framework in a bonded form, so that the lithium ion sieve is not easy to fall off, and the lithium ion sieve is sparsely bonded on the polysulfonamide framework to produce more voids and has a certain hydrophilicity; in addition, the sulfonamide bond -SO2-NH- has a strong affinity with Li +The electrostatic interaction can quickly Li + Capture near the adsorption site, so that Li + Fast into the ion sieve or the internal channel of the amino crown ether, improve the adsorption rate of lithium adsorption material.

[0022] Further, the structural unit B carries the residue of the amino crown ether, which can synergize with the amino-modified lithium ion sieve, and can significantly improve the lithium adsorption capacity of the lithium adsorption material in the solution and the magnesium-lithium selectivity.

[0023] Further, the lithium adsorption material provided by the present application can realize adsorption of lithium under alkaline conditions and desorption under acidic conditions due to the stability of the polysulfonamide skeleton structure and the bonding of the lithium ion sieve with the skeleton, thereby reducing the damage of acid and alkali to the structure of the lithium adsorption material.

[0024] The preparation method of the lithium ion sieve provided by the present application adopts the amino-modified lithium ion sieve, the amino crown ether, the polyamine and the poly-sulfonamide skeleton formed by the polymerization reaction of the poly-sulfonamide skeleton, and the amino-modified lithium ion sieve is connected with the skeleton through a chemical bond, thereby avoiding the problems of poor hydrophilicity and performance decline of the lithium adsorption material caused by the falling of the lithium ion sieve in the prior art. BRIEF DESCRIPTION OF DRAWINGS

[0025] Figure 1 The scanning electron microscope image of the lithium adsorption material prepared in Example 1.

[0026] Figure 2 The scanning electron microscope image of the lithium adsorption material prepared in Comparative Example 4. DETAILED DESCRIPTION

[0027] The endpoints of the ranges and any values disclosed herein are not limited to the precise values stated. The endpoints of the ranges and any values should be understood to be approximate. The exact numerical values should be understood to be approximations that can vary by a small amount depending on the desired or otherwise required precision. Any numerical value, however, can be expressed as approximately the value, and as including all values that are reasonably close, even if the value is not expressly recited. Any numerical value, however, can be expressed as approximately the value, and as including all values that are reasonably close, even if the value is not expressly recited. Any numerical value, however, can be expressed as approximately the value, and as including all values that are reasonably close, even if the value is not expressly recited.

[0028] The first aspect of the present application provides a lithium adsorption material, wherein the lithium adsorption material comprises a polysulfonamide skeleton and an amino-modified lithium ion sieve bonded in the skeleton;

[0029] The lithium ion sieve is connected with the skeleton through the structure shown in formula I;

[0030]

[0031] The polysulfonamide skeleton comprises structural unit A, structural unit B and structural unit C;

[0032] The structural unit A and the structural unit C are connected by the structure shown in formula II;

[0033]

[0034] The structural unit B and the structural unit C are connected by the structure shown in formula III;

[0035]

[0036] Ar1 is the residue of a polyamine; Ar2 is the residue of a poly-sulfonyl chloride; and Ar3 is the residue of an amino crown ether.

[0037] The lithium adsorption material of the present application has a polysulfonamide skeleton comprising structural unit A, structural unit B and structural unit C, and the amino-modified lithium ion sieve is dispersed in the polymer skeleton in a bonded form, so that the lithium ion sieve is not easy to fall off, and the lithium ion sieve is sparsely bonded on the polysulfonamide skeleton, generating more voids and having certain hydrophilicity; furthermore, the electrostatic interaction between the sulfonamide bond -SO2-NH- and Li + can quickly capture Li + near the adsorption site, so that Li + quickly enters the internal pore of the ion sieve or the amino crown ether, improving the adsorption rate of the lithium adsorption material.

[0038] Further, the structural unit B has the residue of an amino crown ether, which can synergize with the amino-modified lithium ion sieve, and can significantly improve the lithium ion adsorption capacity and magnesium-lithium selectivity of the lithium adsorption material in the solution.

[0039] Further, the lithium adsorption material provided by the present application can realize lithium adsorption under alkaline conditions and desorption under acidic conditions due to the stability of the polysulfonamide skeleton structure and the bonding effect of the lithium ion sieve and the skeleton, reducing the structural damage of the lithium adsorption material caused by acid and alkali.

[0040] According to the present application, the polyamine is at least one selected from diethylenetriamine, tetraethylenepentamine, polyethylene polyamine, polyethyleneimine and polyetheramine.

[0041] Further, the polyamine is polyethyleneimine and / or triethylenetetramine.

[0042] According to a preferred embodiment of the present application, the polyamine is polyethyleneimine and triethylenetetramine. Preferably, the content of the structural unit A comprising polyethyleneimine is 45wt%-70wt% based on the weight of the structural unit A. This content range is calculated by the mass of the respective raw materials of the polyamines.

[0043] According to the present application, the weight average molecular weight of the polyethyleneimine or polyetheramine is 80-120 kg / mol.

[0044] Further, the weight average molecular weight of the polyethyleneimine or polyetheramine is 90-110 kg / mol.

[0045] According to the present application, the polybasic sulfuryl chloride is at least one selected from 1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 1,4-benzenedisulfonyl chloride, 2,4-di-sulfonylchloridyl-mesitylene, biphenyl-4,4'-disulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 2,6-naphthalene disulfonyl chloride, 1,3-naphthalene disulfonyl chloride, 2,7-naphthalene disulfonyl chloride, 1,3,5-benzenetrisulfonyl chloride and 1,3,6-naphthalene trisulfonyl chloride.

[0046] Further, the polybasic sulfuryl chloride is 1,3-benzenedisulfonyl chloride and / or 1,2-benzenedisulfonyl chloride.

[0047] Further, the polybasic sulfuryl chloride is 1,3-benzenedisulfonyl chloride and 1,2-benzenedisulfonyl chloride. When Ar2 is the above specific combination, the structure of the lithium adsorption material is more stable. Preferably, the content of the structural unit C containing 1,3-benzenedisulfonyl chloride is 45wt%-55wt% based on the total weight of the structural unit C.

[0048] According to the present application, the amino crown ether is at least one selected from diamino-benzo-14-crown-4, 1-aza-12-crown-4 ether, N,N'-bis(methoxymethyl) dithiaslazadine-12-crown-4, 4',4"(5")-diamino-benzo-15-crown-5 ether, diamino-benzo-15-crown-5 ether, 2-aminomethyl-15-crown-5 and 4'-aminobenzo-18-crown-6.

[0049] In the present application, when the above amino crown ether is used, the lithium adsorption material can significantly improve the adsorption capacity of lithium ions in the solution and the magnesium-lithium selectivity.

[0050] Further, the amino crown ether is diamino-benzo-14-crown-4 and / or 2-aminomethyl-15-crown-5.

[0051] According to the present application, the content of the amino-modified lithium ion sieve is 10wt%-35wt% based on the total weight of the lithium adsorption material, the content of the structural unit A is 11wt%-30wt%, the content of the structural unit B is 4wt%-10wt%, and the content of the structural unit C is 30wt%-70wt%.

[0052] In the present application, when the content of each component in the lithium adsorption material meets the requirements of the present application, the electrostatic interaction between -SO2-NH- in the polysulfonamide skeleton and Li + can quickly capture Li + near the adsorption site, destroy the first water layer associated between SO4 2- and Li + , so that Li + exists in the form of a bare ion, quickly enters the internal pore of the ion sieve or cyclodextrin, and the rate of the adsorption reaction is accelerated.

[0053] In the present application, the saturated adsorption capacity of the lithium adsorption material is directly related to the amino-modified lithium ion sieve in the lithium adsorption material, and it can be understood that only when the content of the amino-modified lithium ion sieve is the same, the saturated adsorption capacity is comparable.

[0054] Further, the content of the amino-modified lithium ion sieve is 19wt%-26wt%, the content of the structural unit A is 12wt%-20wt%, the content of the structural unit B is 4wt%-7wt%, and the content of the structural unit C is 50wt%-60wt%, based on the total weight of the lithium adsorption material.

[0055] According to the present application, the amino-modified lithium ion sieve is a lithium ion sieve modified by an amino silane coupling agent.

[0056] In the present application, the lithium ion sieve modified by the amino silane coupling agent is more conducive to the bonding of the lithium ion sieve in the skeleton and is not easy to fall off, so that the lithium adsorption material has high lithium ion adsorption capacity and magnesium-lithium selectivity.

[0057] According to the present application, the content of the amino silane coupling agent is 0.1wt%-2wt%, based on the weight of the amino-modified lithium ion sieve;

[0058] Further, the content of the amino silane coupling agent is 0.5wt%-1.8wt%, based on the weight of the amino-modified lithium ion sieve.

[0059] According to the present application, the amino silane coupling agent is at least one selected from the group consisting of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane, and 4-amino-3,3-dimethylbutyltrimethoxysilane.

[0060] According to the present application, the lithium ion sieve is selected from a titanium-based lithium ion sieve and / or a manganese-based lithium ion sieve.

[0061] Further, the lithium ion sieve is selected from Li 1.33 Mn 1.67 O4, Li2TiO3, LiTi2O4 and Li4Ti5O 12 .

[0062] According to the present application, the average particle size of the lithium ion sieve is 0.01-500 μm.

[0063] In the present application, when the average particle size of the lithium ion sieve meets the requirements of the present application, the polysulfonamide skeleton and the lithium ion sieve modified by the amino group can play a better synergistic effect, so that the obtained lithium adsorption material has excellent acid and alkali resistance and adsorption performance.

[0064] Further, the average particle size of the lithium ion sieve is 0.03-300 μm.

[0065] According to the present application, the specific surface area of the lithium adsorption material is 8-50 m 2 / g.

[0066] According to the present application, the pore size of the lithium adsorption material is 0.1-8 μm.

[0067] According to the present application, the pore volume of the lithium adsorption material is 15-50 m 3 / g.

[0068] In the present application, when at least one of the specific surface area, the pore size and the pore volume of the lithium adsorption material meets the above characteristics, the acid and alkali resistant lithium adsorption material has high adsorption capacity, strong magnesium and lithium selectivity, high adsorption rate, and good structural stability.

[0069] Further, the specific surface area of the lithium adsorption material is 25-35 m 2 / g.

[0070] Further, the pore size of the lithium adsorption material is 2-4 μm.

[0071] Further, the pore volume of the lithium adsorption material is 30-35 m 3 / g.

[0072] According to the present application, the average particle size of the lithium adsorption material is 0.8-3 mm.

[0073] In the present application, the lithium adsorption material can be regular and / or irregular in shape. When the average particle size of the lithium adsorption material meets the above-mentioned limitation, the lithium ion sieve modified by the poly-sulfonamide skeleton and the amino group can play a better synergistic effect, so that the obtained lithium adsorption material has excellent acid and alkali resistance and adsorption performance.

[0074] Further, the average particle size of the lithium adsorption material is 1-1.5 mm.

[0075] The second aspect of the present application provides a lithium adsorption material and a preparation method thereof, comprising the following steps:

[0076] (1) The lithium ion sieve is modified by the amino group to obtain the lithium ion sieve modified by the amino group;

[0077] (2) The lithium ion sieve modified by the amino group, the polyamine and the amino crown ether are uniformly mixed in water to obtain a mixed solution 1;

[0078] (3) Under stirring, the organic solution containing the poly-sulfonyl chloride is dropped into the mixed solution 1 to obtain a mixed solution 2 for reaction, and the product after reaction is subjected to heat treatment to obtain a semi-solid cross-linked product, and the lithium adsorption material is obtained after extrusion.

[0079] The preparation method of the lithium ion sieve provided by the present application adopts the lithium ion sieve modified by the amino group, the amino crown ether, the polyamine and the poly-sulfonyl chloride, and the poly-sulfonamide skeleton is formed through polymerization reaction, and the lithium ion sieve modified by the amino group is connected to the skeleton through a chemical bond, which avoids the problems in the prior art, such as poor resistance to strong acid and strong alkali, poor hydrophilicity of the lithium adsorption material, and performance degradation of the lithium adsorption material caused by the falling of the lithium ion sieve during use.

[0080] According to the present application, the lithium ion sieve is selected from a titanium-based lithium ion sieve and / or a manganese-based lithium ion sieve.

[0081] Further, the above-mentioned lithium ion sieve is selected from at least one of Li 1.33 Mn 1.67 O4, Li2TiO3, LiTi2O4 and Li4Ti5O 12 .

[0082] The lithium ion sieve in the present application is not particularly limited in source, and can be obtained by commercial purchase or self-preparation. Preferably, the preparation of the lithium ion sieve comprises: sequentially subjecting a mixed solution of a titanium source, a lithium source and an organic solvent to ball milling, drying, calcination and acid washing, to obtain the lithium ion sieve. Preferably, the molar ratio of the titanium source to the lithium source is 1:0.95-1.05. Preferably, the mass ratio of the combination of the titanium source and the lithium source to the organic solvent is 1:1.5-3. Preferably, the ball milling conditions comprise: a ball milling speed of 100-300 rpm and a ball milling time of 2-6 h. Preferably, the calcination conditions comprise: a calcination temperature of 700-900 DEG C under an air atmosphere and a calcination time of 4-8 h. Preferably, the acid liquid is selected from hydrochloric acid and / or sulfuric acid. Preferably, the concentration of the acid liquid is 0.01-1 mol / L. Preferably, the washing time is 0.5-24 h.

[0083] According to the present application, the average particle size of the lithium ion sieve is 0.01-500 mu m.

[0084] In the present application, when the average particle size of the lithium adsorption material meets the above limitation, the poly-sulfonamide skeleton and the amino-modified lithium ion sieve can play a better synergistic effect, so that the obtained lithium adsorption material has excellent acid and alkali resistance and adsorption performance.

[0085] Further, the average particle size of the lithium ion sieve is 0.03-300 mu m.

[0086] According to the present application, the lithium ion sieve is modified by amino silane coupling agent.

[0087] According to the present application, the amino silane coupling agent is selected from at least one of gamma-aminopropyltrimethoxysilane, gamma-aminopropyltriethoxysilane, N-(beta-aminoethyl)-gamma-aminopropyltrimethoxysilane, N-(beta-aminoethyl)-gamma-aminopropyltriethoxysilane, N-(beta-aminoethyl)-gamma-aminopropylmethyldimethoxysilane, gamma-aminopropylmethyldiethoxysilane, gamma-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane.

[0088] According to the present application, the mass ratio of the lithium ion sieve to the amino silane coupling agent is 1:0.5-2.

[0089] Further, the mass ratio of the lithium ion sieve to the amino silane coupling agent is 1:0.5-1.8.

[0090] According to the present application, the amino modification conditions comprise: a pH value of 1-3, a reaction temperature of 40-95 DEG C and a reaction time of 0.5-12 h.

[0091] According to the present application, in step (3), the content of the amino-modified lithium ion sieve is 10wt%-35wt%, the content of the polyamine is 11wt%-30wt%, the content of the amino crown ether is 4wt%-10wt%, and the content of the poly-sulfonyl chloride is 30wt%-70wt%, based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether and the poly-sulfonyl chloride.

[0092] In the present application, when the content of each component meets the above-mentioned limitation, the -SO2-NH- in the poly-sulfonamide skeleton formed can quickly capture Li + by the electrostatic interaction with Li + , destroy the first water and layer formed by the association between SO4 2- and Li + , and make Li + exist in the form of a bare ion, quickly enter the internal pore of the ion sieve or the cyclodextrin, and accelerate the rate of the adsorption reaction.

[0093] Further, the content of the amino-modified lithium ion sieve is 19wt%-26wt%, the content of the polyamine is 12wt%-20wt%, the content of the amino crown ether is 4wt%-7wt%, and the content of the poly-sulfonyl chloride is 50wt%-60wt%, based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether and the poly-sulfonyl chloride.

[0094] According to the present application, the polyamine is at least one selected from diethylene triamine, tetraethylene pentamine, polyethylene polyamine, polyethylene imine and polyether amine.

[0095] Further, the polyamine is polyethylene imine and / or triethylene tetramine.

[0096] According to a preferred embodiment of the present application, the polyamine is a combination of polyethylene imine and triethylene tetramine. Preferably, the mass ratio of the polyethylene imine and triethylene tetramine is 1-2.5:1.

[0097] According to the present application, the weight average molecular weight of the polyethylene imine or polyether amine is 80-120 kg / mol.

[0098] Further, the weight average molecular weight of the polyethylene imine or polyether amine is 90-110 kg / mol.

[0099] According to the present application, the amino crown ether is at least one selected from the group consisting of diamino-benzo-14-crown-4, 1-aza-12-crown-4 ether, N,N'-bis(methoxymethyl) dithiaslazadine-12-crown-4, 4',4"(5")-diamino-benzo-15-crown-5 ether, diamino-benzo-15-crown-5 ether, 2-aminomethyl-15-crown-5 and 4'-aminobenzo-18-crown-6.

[0100] In the present application, when the above-mentioned amino crown ether is used, the lithium adsorption material can significantly improve the adsorption capacity, adsorption rate and magnesium-lithium selectivity of lithium ions in the solution.

[0101] Further, the amino crown ether is diamino-benzo-14-crown-4 and / or 2-aminomethyl-15-crown-5.

[0102] According to the present application, the polybasic sulfuryl chloride is at least one selected from the group consisting of 1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 1,4-benzenedisulfonyl chloride, 2,4-dichlorobenzene-1,3,5-trisulfonyl chloride, diphenyl-4,4'-disulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 2,6-naphthalene disulfonyl chloride, 1,3-naphthalene disulfonyl chloride, 2,7-naphthalene disulfonyl chloride, 1,3,5-benzenetrisulfonyl chloride and 1,3,6-naphthalene trisulfonyl chloride.

[0103] Further, the polybasic sulfuryl chloride is 1,3-benzenedisulfonyl chloride and / or 1,2-benzenedisulfonyl chloride.

[0104] Further, the polybasic sulfuryl chloride is 1,3-benzenedisulfonyl chloride and 1,2-benzenedisulfonyl chloride. Preferably, the mass ratio of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride is 1-1.5:1.

[0105] In the present application, the content of the polybasic sulfuryl chloride in the organic solution containing the polybasic sulfuryl chloride is 0.25wt%-10wt%. The type of the organic solvent is not particularly limited, and a conventional type of organic solvent in the art can be used, such as one or more of n-hexane, dodecane, n-heptane, and alkane solvent oil (Isopar E, Isopar G, Isopar H, Isopar L and Isopar M).

[0106] Further, the content of the polybasic sulfuryl chloride in the organic solution containing the polybasic sulfuryl chloride is 0.5wt%-5wt%.

[0107] According to the present application, the reaction conditions include that the reaction temperature is 10-70℃, and the reaction time is 5-300min.

[0108] When the reaction conditions are used, the polymeric reaction between the components is facilitated to form a poly-sulfonamide skeleton, so that the prepared lithium adsorption material has high lithium ion adsorption capacity in solution and high magnesium-lithium selectivity.

[0109] Further, the reaction conditions include that the reaction temperature is 30-50℃ and the reaction time is 10-60min.

[0110] According to the application, the heat treatment conditions include that the heat treatment temperature is 80-150℃ and the heat treatment time is 5-60min.

[0111] Further, the heat treatment conditions include that the heat treatment temperature is 90-120℃ and the heat treatment time is 10-30min.

[0112] According to the application, the preparation method further includes that the lithium adsorption material is eluted by using an acidic solution.

[0113] According to the application, the acidic solution is selected from hydrochloric acid and / or sulfuric acid.

[0114] According to the application, the concentration of the acidic solution is 0.01-1mol / L.

[0115] According to the application, the elution time is 0.5-24h.

[0116] The third aspect of the application provides a lithium adsorption material prepared by the above preparation method.

[0117] The fourth aspect of the application provides an application of the above lithium adsorption material in lithium extraction from salt lake.

[0118] According to the application, the magnesium-lithium ratio of the salt lake is 10-500:1. The lithium adsorption material of the application has excellent magnesium-lithium selectivity and can adsorb lithium ions in the salt lake with high magnesium-lithium ratio.

[0119] According to the application, the ratio of the sulfate ion concentration to the lithium ion concentration in the salt lake is 200-700:1. The lithium adsorption material of the application can destroy the electrostatic interaction between SO4 2- and Li + , so that Li + exists in the form of a bare ion, thereby enabling Li + to quickly enter the internal pore channel of the ion sieve or aminocrown ether and adsorb lithium ions in the sulfate type salt lake.

[0120] The application will be described in detail below through examples.

[0121] Dynamic adsorption-desorption cycle method: The lithium adsorption material (4 g) obtained from the examples and comparative examples was loaded into a glass column and acid washed, and 0.5 M hydrochloric acid (200 mL) was pumped into the column at a flow rate of 2 BV / h at 30°C for 24 h to wash and remove lithium ions in the material. After washing with deionized water to neutralize, the lithium adsorbent to be tested was obtained. The adsorption was carried out by pumping 500 mL of a mixed solution (lithium ion 40 mg / L, magnesium ion 1093 mg / L, chloride ion 14230 mg / L, sulfate ion 19200 mg / L, magnesium-lithium ratio 27.3, pH = 9.5, 30°C) into the column at a flow rate of 2 BV / h using a peristaltic pump, and then the desorption was carried out by pumping 250 mL of 0.5 M hydrochloric acid into the column at a flow rate of 2 BV / h using a peristaltic pump for 8 h to obtain a desorption solution of one dynamic cycle, which is referred to as the first dynamic adsorption-desorption cycle.

[0122] Static adsorption-desorption cycle method: 0.5 g of the lithium adsorption material to be tested was subjected to static adsorption with 40 mL of a mixed solution (lithium ion 40 mg / L, magnesium ion 1093 mg / L, chloride ion 14230 mg / L, sulfate ion 19200 mg / L, magnesium-lithium ratio 27.3, pH = 9.5, 30°C). After the concentrations of lithium ions and magnesium ions in the lithium-magnesium mixed solution did not change, 100 mL of 0.5 M HC1 was used for desorption for 24 h to obtain a static cycle desorption solution.

[0123] Saturation adsorption capacity determination of lithium adsorption material: The static adsorption-desorption cycle method described above was used. After the lithium adsorption material to be tested was statically adsorbed to equilibrium, the lithium adsorption material to be tested was separated from the mixed solution, and the saturation adsorption capacity Q was calculated according to the following formula.

[0124]

[0125] Wherein, Q is the saturation adsorption capacity, with a unit of mg / g, reflecting the adsorption amount of the lithium adsorption material when the adsorption reaches equilibrium; C0 and C are the lithium ion concentrations in the lithium-magnesium mixed solution at the start and when the lithium adsorption material to be tested is saturated with adsorption, respectively, with a unit of mg / L; V is the volume of the lithium-magnesium mixed solution, with a unit of L; and M is the mass of the lithium adsorption material to be tested, with a unit of g.

[0126] 90% adsorption capacity time of lithium adsorption material: The static adsorption-desorption cycle method described above was used. During the adsorption process, the concentrations of magnesium ions and lithium ions in the lithium-magnesium mixed solution were monitored to monitor the change of the adsorption capacity with time; the 90% adsorption capacity time was the time required for the adsorption capacity to reach 90% of the saturation adsorption capacity. The 90% adsorption capacity time could reflect the speed of the lithium adsorption material, and the shorter the time required, the faster the adsorption speed.

[0127] Cycling stability of lithium adsorbent material: after the lithium adsorbent material is cycled for 30 times according to the dynamic adsorption-desorption cycling method described above, the percentage decrease of the adsorption capacity after 30 times is calculated to evaluate the cycling stability of the lithium adsorbent material.

[0128] Mass loss ratio of lithium adsorbent material: the mass loss ratio is determined by weighing method, i.e. the mass of the lithium adsorbent material before use (i.e. initial mass) and the mass of the lithium adsorbent material after 30 times of dynamic adsorption-desorption cycling are weighed respectively, and the ratio of the mass loss to the initial mass is the mass loss ratio.

[0129] Magnesium-lithium ratio of desorption solution of lithium adsorbent material: the concentration of magnesium ions and the concentration of lithium ions in the desorption solution sample in one dynamic cycle of the dynamic adsorption-desorption cycling method described above are determined to obtain the ratio of the concentrations of magnesium ions and lithium ions.

[0130] The morphology of the lithium adsorbent material is characterized by scanning electron microscopy (SEM, S-4800).

[0131] The concentration of magnesium ions or lithium ions is determined by ion chromatography (ICS-1100, DIONEX, America).

[0132] Specific surface area, pore size, and pore volume of lithium adsorbent material: BET method is used for determination, and the specific method is as follows: at 77 K, the adsorption-desorption isotherm of N2 of the lithium adsorbent material is determined (the lithium adsorbent material is degassed by heating and vacuumizing to remove the impurity gas adsorbed on the surface. Then it is weighed and placed in liquid nitrogen. At different pressure points set in advance, the nitrogen adsorption amount of the sample is determined at liquid nitrogen temperature to obtain the adsorption isotherm), and the BET specific surface area, pore size, and pore volume are fitted.

[0133] The average particle size of the lithium adsorbent material is determined by scanning electron microscopy.

[0134] In the lithium adsorbent material, the content of the amino-modified lithium ion sieve and each structural unit is calculated by the feeding ratio of the raw materials corresponding to each structural unit.

[0135] In the amino-modified lithium ion sieve, the content of the amino silane coupling agent is determined by weight gain method.

[0136] The raw materials in the following preparation examples, examples, and comparative examples are commercially available.

[0137] Preparation Example 1

[0138] Amino-modified lithium ion sieve: Lithium ion sieve powder Li2TiO3(0.1 μm) was ground in a ball mill for 12 h to improve dispersibility. 1 g of the ground powder was dissolved in 1 L of ultrapure water at 80 °C, and 1 g of γ-aminopropyltrimethoxysilane was added to the system, with a mass ratio of lithium ion sieve to amino silane coupling agent of 1:1. Hydrochloric acid was used to adjust the pH to 2, and continuous stirring was performed at 80 °C for 6 h to obtain the amino-modified lithium ion sieve. The product was centrifuged at room temperature and then washed with pure water three times. Ball milling was performed at room temperature for 6 h, and then the product was dried. Amino-modified lithium ion sieve A was obtained, and the content of amino silane coupling agent in the amino-modified lithium ion sieve A was 0.14 wt%.

[0139] Preparation Example 2

[0140] Preparation of modified lithium ion sieve: Lithium ion sieve powder Li2TiO3(0.1 μm) was ground in a ball mill for 12 h to improve dispersibility. 1 g of the ground powder was dissolved in 1 L of ultrapure water at 80 °C, and 0.8 g of γ-aminopropyltrimethoxysilane was added to the system, with a mass ratio of lithium ion sieve to amino silane coupling agent of 1:0.8. Hydrochloric acid was used to adjust the pH to 2, and continuous stirring was performed at 80 °C for 6 h to obtain the modified lithium ion sieve. The product was centrifuged at room temperature and then washed with pure water three times. Ball milling was performed at room temperature for 6 h, and then the product was dried. Amino-modified lithium ion sieve B was obtained, and the content of amino silane coupling agent in the amino-modified lithium ion sieve B was 0.12 wt%.

[0141] Preparation Example 3

[0142] Preparation of modified lithium ion sieve: Lithium ion sieve powder Li2TiO3(0.1 μm) was ground in a ball mill for 12 h to improve dispersibility. 1 g of the ground powder was dissolved in 1 L of ultrapure water at 80 °C, and 1.5 g of γ-aminopropyltrimethoxysilane was added to the system, with a mass ratio of lithium ion sieve to amino silane coupling agent of 1:1.5. Hydrochloric acid was used to adjust the pH to 2, and continuous stirring was performed at 80 °C for 6 h to obtain the modified lithium ion sieve. The product was centrifuged at room temperature and then washed with pure water three times. Ball milling was performed at room temperature for 6 h, and then the product was dried. Amino-modified lithium ion sieve C was obtained, and the content of amino silane coupling agent in the amino-modified lithium ion sieve C was 1.8 wt%.

[0143] Preparation Example 4

[0144] Preparation of modified lithium ion sieve: Lithium ion sieve powder Li2TiO3(0.1 μm) was ground in a ball mill for 12 h to improve dispersibility. 1 g of the ground powder was dissolved in 1 L of ultrapure water at 80 °C, and 1 g of mercaptopropyl trimethoxysilane was added to the system. The mass ratio of lithium ion sieve to coupling agent was 1:1. Hydrochloric acid was used to adjust the pH to 2, and the system was continuously stirred at 80 °C for 6 h to obtain the modified lithium ion sieve. The product was centrifuged at room temperature and then washed with pure water three times. Ball milling was performed at room temperature for 6 h, and the product was dried. Modified lithium ion sieve E was obtained, and the content of mercaptopropyl trimethoxysilane coupling agent in the modified lithium ion sieve E was 0.11 wt%.

[0145] Preparation Example 5

[0146] Preparation of modified lithium ion sieve: Lithium ion sieve powder Li2TiO3(0.1 μm) was ground in a ball mill for 12 h to improve dispersibility. 1 g of the ground powder was dissolved in 1 L of ultrapure water at 80 °C, and 1 g of mercaptopropyl trimethoxysilane was added to the system. The mass ratio of lithium ion sieve to coupling agent was 1:1. Hydrochloric acid was used to adjust the pH to 2, and the system was continuously stirred at 80 °C for 6 h to obtain the modified lithium ion sieve. The product was centrifuged at room temperature and then washed with pure water three times. Ball milling was performed at room temperature for 6 h, and the product was dried. Modified lithium ion sieve E was obtained, and the content of mercaptopropyl trimethoxysilane coupling agent in the modified lithium ion sieve E was 0.11 wt%.

[0147] Example 1

[0148] (1) Amino-modified Li 1.33 Mn 1.67 O4(100 nm) lithium ion sieve A was uniformly dispersed in an aqueous solution by ultrasonic dispersion, and polyethyleneimine (Mw = 100,000 g / mol), triethylenetetramine, and diaminobis-14-crown-4 were added. After stirring for 24 h, a mixed solution 1 was obtained (the mass ratio of polyethyleneimine to triethylenetetramine was 2:1);

[0149] (2) Under mechanical stirring, the same volume of 13 wt% 1,2-benzenedisulfonyl chloride and 12 wt% 1,3-benzenedisulfonyl chloride Isopar E solution was added dropwise into the above mixed solution 1 to obtain a mixed solution 2 (based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether, and the polymeric sulfonamide chloride, the content of the amino-modified lithium ion sieve was 24.49 wt%, the content of the polyamine was 18.37 wt%, the content of the amino crown ether was 6.12 wt%, and the content of the polymeric sulfonamide chloride was 51.02 wt%). After reaction at 50 °C for 120 min, the semi-solid crosslinked product was obtained by heat treatment at 90 °C for 60 min, and the lithium adsorption material with an average particle size of 1.5 mm was obtained by extrusion through an extruder.

[0150] The prepared skeleton has Ar1 as the residue of polyethyleneimine and triethylenetetramine, wherein the content of the structural unit A containing polyethyleneimine is 66.7 wt% based on the total weight of the structural unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, wherein the content of the structural unit C containing 1,3-benzenedisulfonyl chloride is 48 wt% based on the total weight of the structural unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0151] Example 2

[0152] (1) The amino-modified Li 1.33 Mn 1.67 O4(100 nm) was uniformly dispersed in an aqueous solution by ultrasonic dispersion, polyethyleneimine (Mw = 100,000 g / mol), triethylenetetramine, and diaminodibenzo-14-crown-4 were added, and stirring was performed for 24 h to obtain a mixed solution 1 (the mass ratio of polyethyleneimine to triethylenetetramine was 2:1);

[0153] (2) Under mechanical stirring, the same volume of 20 wt% 1,2-benzenedisulfonyl chloride and 20 wt% 1,3-benzenedisulfonyl chloride Isopar E solutions were added dropwise into the above-mentioned mixed solution 1 to obtain a mixed solution 2 (based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether, and the polymeric sulfonyl chloride, the content of the amino-modified lithium ion sieve was 25.35 wt%, the content of the polyamine was 12.68 wt%, the content of the amino crown ether was 5.63 wt%, and the content of the polymeric sulfonyl chloride was 56.34 wt%). After reaction at 50°C for 120 min and heat treatment at 90°C for 60 min, a semi-solid crosslinked product was obtained, which was extruded through an extruder to obtain a lithium adsorption material with an average particle size of 1.5 mm.

[0154] The prepared skeleton has Ar1 as the residue of polyethyleneimine and triethylenetetramine, wherein the content of the structural unit A containing polyethyleneimine is 66.7 wt% based on the total weight of the structural unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, wherein the content of the structural unit C containing 1,3-benzenedisulfonyl chloride is 50 wt% based on the total weight of the structural unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0155] Example 3

[0156] (1) The amino-modified Li 1.33 Mn 1.67O4(100 nm) lithium ion sieve A was uniformly dispersed in an aqueous solution by ultrasonic dispersion, polyethyleneimine (Mw = 1 million g / mol), triethylenetetramine, and diaminodibenzo-14-crown-4 were added, and stirring was performed for 24 h to obtain a mixed solution 1 (the mass ratio of polyethyleneimine and triethylenetetramine was 1:1);

[0157] (2) Under mechanical stirring, the same volume of 18 wt% 1,2-benzenedisulfonyl chloride and 17 wt% 1,3-benzenedisulfonyl chloride Isopar E solutions were added dropwise into the above-mentioned mixed solution 1 to obtain a mixed solution 2 (based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether, and the polymeric sulfonamide, the content of the amino-modified lithium ion sieve was 19.35 wt%, the content of the polyamine was 19.35 wt%, the content of the amino crown ether was 4.84 wt%, and the content of the polymeric sulfonamide was 56.46 wt%). After reaction at 50°C for 120 min, semi-solid crosslinked products were obtained by heat treatment at 90°C for 60 min, and then extruded through an extruder to obtain lithium adsorption materials with an average particle size of 1.5 mm.

[0158] In the prepared skeleton, Ar1 is the residue of polyethyleneimine and triethylenetetramine, wherein the content of the structure unit A containing polyethyleneimine is 50 wt% based on the total weight of the structure unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, wherein the content of the structure unit C containing 1,3-benzenedisulfonyl chloride is 48.6 wt% based on the total weight of the structure unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0159] Example 4

[0160] (1) The amino-modified Li 1.33 Mn 1.67 O4(100 nm) lithium ion sieve A was uniformly dispersed in an aqueous solution by ultrasonic dispersion, polyethyleneimine (Mw = 1 million g / mol), triethylenetetramine, and diaminodibenzo-14-crown-4 were added, and stirring was performed for 24 h to obtain a mixed solution 1 (the mass ratio of polyethyleneimine and triethylenetetramine was 1:1);

[0161] (2) Under mechanical stirring, the same volume of 20 wt% 1,2-benzenedisulfonyl chloride and 20 wt% 1,3-benzenedisulfonyl chloride Isopar E solution was dropped into the above-mentioned mixed solution 1 to obtain mixed solution 2 (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and poly-sulfonyl chloride, the content of the amino-modified lithium ion sieve was 25 wt%, the content of the polyamine was 13.89 wt%, the content of the amino crown ether was 5.56 wt%, and the content of the poly-sulfonyl chloride was 55.55 wt%). After 120 min of reaction at 50°C, semi-solid cross-linked product was obtained by heat treatment at 90°C for 60 min, and then extruded through an extruder to obtain lithium adsorption material with an average particle size of 1.5 mm.

[0162] In the prepared skeleton, Ar1 is the residue of polyethyleneimine and triethylenetetramine, wherein the content of the structure unit A containing polyethyleneimine is 50 wt% based on the total weight of the structure unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, wherein the content of the structure unit C containing 1,3-benzenedisulfonyl chloride is 50 wt% based on the total weight of the structure unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0163] Example 5

[0164] (1) The amino-modified Li 1.33 Mn 1.67 O4(100 nm) lithium ion sieve A was uniformly dispersed in an aqueous solution, polyethyleneimine (Mw = 10 million g / mol), triethylenetetramine and diaminodibenzo-14-crown-4 were added, and stirred for 24 h to obtain mixed solution 1 (the mass ratio of polyethyleneimine and triethylenetetramine was 1:1);

[0165] (2) Under mechanical stirring, the same volume of 20 wt% 1,2-benzenedisulfonyl chloride and 20 wt% 1,3-benzenedisulfonyl chloride Isopar E solution was dropped into the above-mentioned mixed solution 1 to obtain mixed solution 2 (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and poly-sulfonyl chloride, the content of the amino-modified lithium ion sieve was 25 wt%, the content of the polyamine was 13.89 wt%, the content of the amino crown ether was 5.56 wt%, and the content of the poly-sulfonyl chloride was 55.55 wt%). After 120 min of reaction at 50°C, semi-solid cross-linked product was obtained by heat treatment at 90°C for 60 min, and then extruded through an extruder to obtain lithium adsorption material with an average particle size of 1.5 mm.

[0166] The prepared skeleton has Ar1 as the residue of polyethyleneimine and triethylenetetramine, wherein the content of the structural unit A containing polyethyleneimine is 50 wt% based on the total weight of the structural unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, wherein the content of the structural unit C containing 1,3-benzenedisulfonyl chloride is 50 wt% based on the total weight of the structural unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0167] Example 6

[0168] (1) The amino-modified Li 1.33 Mn 1.67 O4(100 nm) was uniformly dispersed in an aqueous solution by ultrasonic dispersion, polyethyleneimine (Mw = 10 million g / mol), triethylenetetramine and diaminodibenzo-14-crown-4 were added, and stirring was performed for 24 h to obtain a mixed solution 1 (the mass ratio of polyethyleneimine and triethylenetetramine was 1:1);

[0169] (2) Under mechanical stirring, the same volume of 10 wt% 1,2-benzenedisulfonyl chloride and 10 wt% 1,3-benzenedisulfonyl chloride Isopar E solutions were dropped into the above-mentioned mixed solution 1 to obtain a mixed solution 2 (based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether and the polymeric sulfonyl chloride, the content of the amino-modified lithium ion sieve was 33.33 wt%, the content of the polyamine was 27.27 wt%, the content of the amino crown ether was 9.09 wt%, and the content of the polymeric sulfonyl chloride was 30.31 wt%). After reaction at 50°C for 120 min and heat treatment at 90°C for 60 min, a semi-solid crosslinked product was obtained, which was extruded through an extruder to obtain a lithium adsorption material with an average particle size of 1.5 mm.

[0170] The prepared skeleton has Ar1 as the residue of polyethyleneimine and triethylenetetramine, wherein the content of the structural unit A containing polyethyleneimine is 50 wt% based on the total weight of the structural unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, wherein the content of the structural unit C containing 1,3-benzenedisulfonyl chloride is 50 wt% based on the total weight of the structural unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0171] Example 7

[0172] (1) The amino-modified Li 1.33 Mn 1.67O4(100 nm) lithium ion sieve A was uniformly dispersed in aqueous solution by ultrasonic dispersion, polyethyleneimine (Mw = 100,000 g / mol), triethylenetetramine and diaminodibenzo-14-crown-4 were added, stirred for 24 h to obtain mixed solution 1 (the mass ratio of polyethyleneimine and triethylenetetramine was 1:1);

[0173] (2) Under mechanical stirring, the same volume of 9 wt% 1,2-benzenedisulfonyl chloride and 9 wt% 1,3-benzenedisulfonyl chloride Isopar E solution was dropped into the above-mentioned mixed solution 1 to obtain mixed solution 2 (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polymeric sulfonamide, the content of the amino-modified lithium ion sieve was 32.05 wt%, the content of the polyamine was 32.05 wt%, the content of the amino crown ether was 12.82 wt%, and the content of the polymeric sulfonamide was 23.08 wt%). After reaction at 50°C for 120 min, semi-solid cross-linked product was obtained by heat treatment at 90°C for 60 min, and then extruded through an extruder to obtain lithium adsorption material with an average particle size of 1.5 mm.

[0174] In the prepared skeleton, Ar1 is the residue of polyethyleneimine and triethylenetetramine, wherein the content of the structure unit A containing polyethyleneimine is 50 wt% based on the total weight of the structure unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, wherein the content of the structure unit C containing 1,3-benzenedisulfonyl chloride is 50 wt% based on the total weight of the structure unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0175] Example 8

[0176] The lithium adsorption material was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced by the amino-modified lithium ion sieve B.

[0177] In the prepared skeleton, Ar1 is the residue of polyethyleneimine and triethylenetetramine, wherein the content of the structure unit A containing polyethyleneimine is 66.7 wt% based on the total weight of the structure unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, wherein the content of the structure unit C containing 1,3-benzenedisulfonyl chloride is 48 wt% based on the total weight of the structure unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0178] Example 9

[0179] The lithium adsorption material was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced by the amino-modified lithium ion sieve C.

[0180] The obtained skeleton is obtained, wherein Ar1 is the residue of polyethyleneimine and triethylenetetramine, the content of the structural unit A containing polyethyleneimine is 66.7 wt% based on the total weight of the structural unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, the content of the structural unit C containing 1,3-benzenedisulfonyl chloride is 48 wt% based on the total weight of the structural unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0181] Example 10

[0182] The lithium adsorption material is prepared according to the method of Example 1, except that the modified lithium ion sieve A is replaced by the amino-modified lithium ion sieve D.

[0183] The obtained skeleton is obtained, wherein Ar1 is the residue of polyethyleneimine and triethylenetetramine, the content of the structural unit A containing polyethyleneimine is 66.7 wt% based on the total weight of the structural unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, the content of the structural unit C containing 1,3-benzenedisulfonyl chloride is 48 wt% based on the total weight of the structural unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0184] Example 11

[0185] (1) The amino-modified Li 1.33 Mn 1.67 O4(100 nm) lithium ion sieve A is uniformly dispersed in an aqueous solution by ultrasonic dispersion, polyethyleneimine (Mw = 100,000 g / mol) and diaminodibenzo-14-crown-4 are added, and stirring is performed for 24 h to obtain a mixed solution 1;

[0186] (2) Under mechanical stirring, the same volume of 13 wt% 1,2-benzenedisulfonyl chloride and 12 wt% 1,3-benzenedisulfonyl chloride Isopar E solutions are added dropwise into the above-mentioned mixed solution 1 to obtain a mixed solution 2 (based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether and the polymeric sulfonyl chloride, the content of the amino-modified lithium ion sieve is 24.49 wt%, the content of the polyamine is 18.37 wt%, the content of the amino crown ether is 6.12 wt%, and the content of the polymeric sulfonyl chloride is 51.02 wt%). After reaction at 50°C for 120 min and heat treatment at 90°C for 60 min, a semi-solid crosslinked product is obtained, which is extruded through an extruder to obtain a lithium adsorption material with an average particle size of 1.5 mm.

[0187] The obtained skeleton is prepared, Ar1 is the residue of polyethyleneimine; Ar2 is the residue of 1,2-benzenedisulfonyl chloride and 1,3-benzenedisulfonyl chloride, wherein the content of the structural unit C containing 1,3-benzenedisulfonyl chloride is 48% by weight based on the total weight of the structural unit C; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0188] Example 12

[0189] (1) The amino-modified Li 1.33 Mn 1.67 O4(100 nm) is uniformly dispersed in an aqueous solution by ultrasonic dispersion, polyethyleneimine (Mw = 100,000 g / mol) and diaminodibenzo-14-crown-4 are added, and stirring is performed for 24 h to obtain a mixed solution 1 (the mass ratio of polyethyleneimine to triethylenetetramine is 2:1);

[0190] (2) Under mechanical stirring, 25% by weight of a 1,2-benzenedisulfonyl chloride Isopar E solution is added dropwise into the above-mentioned mixed solution 1 to obtain a mixed solution 2 (the content of the amino-modified lithium ion sieve is 24.49% by weight, the content of the polyamine is 18.37% by weight, the content of the amino crown ether is 6.12% by weight, and the content of the polymeric sulfonyl chloride is 51.02% by weight based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether, and the polymeric sulfonyl chloride). After reaction at 50°C for 120 min and heat treatment at 90°C for 60 min, a semi-solid crosslinked product is obtained, which is extruded through an extruder to obtain a lithium adsorption material with an average particle size of 1.5 mm.

[0191] The obtained skeleton is prepared, Ar1 is the residue of polyethyleneimine and triethylenetetramine, wherein the content of the structural unit A containing polyethyleneimine is 66.7% by weight based on the total weight of the structural unit A; Ar2 is the residue of 1,2-benzenedisulfonyl chloride; and Ar3 is the residue of diaminodibenzo-14-crown-4.

[0192] Comparative Example 1

[0193] The lithium adsorption material is prepared according to the method of Example 1, except that diaminodibenzo-14-crown-4 is not added, and the content of the amino-modified lithium ion sieve, the polyamine, and the polymeric sulfonyl chloride is 24.49% by weight, 19.57% by weight, and 55.94% by weight, respectively, based on the total weight of the amino-modified lithium ion sieve, the polyamine, and the polymeric sulfonyl chloride.

[0194] Comparative Example 2

[0195] The lithium adsorption material is prepared according to the method of Example 1, except that the unmodified Li 1.33 Mn 1.67O4 (100 nm) lithium ion sieve.

[0196] Comparative Example 3

[0197] The lithium adsorption material was prepared according to the method of Example 1, except that no polyethyleneimine (Mw = 1 million g / mol) and triethylenetetramine were added in step (1). No shaped material was obtained.

[0198] Comparative Example 4

[0199] A water solution of polyethyleneimine (Mw = 1 million g / mol), triethylenetetramine was mixed with a 13 wt% solution of 1,2-benzenedisulfonyl chloride and a 12 wt% solution of 1,3-benzenedisulfonyl chloride in Isopar G. The reaction temperature was 60°C and the reaction time was 10 min, and a semi-solid product was obtained. The semi-solid product was then mixed with diamino-dibenzo-14-crown-4 and amino-modified lithium ion sieve A, and extruded after drying. The content of the amino-modified lithium ion sieve was 24.49 wt%, the content of the polyamine was 18.37 wt%, the content of the amino crown ether was 6.12 wt%, and the content of the poly-sulfonyl chloride was 51.02 wt%, based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether and the poly-sulfonyl chloride.

[0200] Comparative Example 5

[0201] The lithium adsorption material was prepared according to the method of Example 1, except that the amino-modified lithium ion sieve A was replaced with modified lithium ion sieve E.

[0202] In the present application, the contents of the amino-modified lithium ion sieve, the structural unit A, the structural unit B and the structural unit C in the lithium adsorption materials prepared in Examples 1-12, Comparative Examples 1-2 and 3-4 are shown in Table 1. The specific surface area, pore size, pore volume and average particle size of the lithium adsorption materials of Examples 1-12 and Comparative Examples 1-5 are shown in Table 2. The test results of the 90% adsorption capacity time, the saturated adsorption capacity, the magnesium-lithium ratio of the desorption solution, the mass loss ratio and the percentage decrease in adsorption capacity after 30 desorption cycles of the lithium adsorption materials of Examples 1-12, Comparative Examples 1-2 and 4-5 are shown in Table 3.

[0203] Table 1

[0204]

[0205] Table 2

[0206]

[0207]

[0208] Table 3

[0209]

[0210] The results show that the comprehensive performance of the lithium adsorption material obtained using the solution of the present invention is superior to that of the comparative example. The adsorption time for the lithium adsorption material of the present invention to reach 90% of the adsorption capacity is within 70 minutes, indicating that the prepared adsorption material has a fast adsorption rate; at the same time, the magnesium-lithium ratio of the desorption solution is low, indicating that the lithium adsorption material of the present invention has excellent magnesium-lithium selectivity. After 30 cycles of adsorption under alkaline conditions and desorption under acidic conditions, the strength and stability of the lithium adsorption materials of Examples 1-12 remain unchanged, that is, the mass loss ratio of the lithium adsorption material is less than or equal to 1%, and the percentage decrease in adsorption capacity after 30 desorption cycles is less than or equal to 1%, indicating that the lithium adsorption material of the present invention has a stable structure.

[0211] When the addition amount of the amino-modified lithium ion sieve is the same, compared with Comparative Example 1, the adsorption capacity of the lithium adsorption material of the embodiment is increased, and the magnesium-lithium ratio in the desorption liquid is low, indicating that under the synergistic effect of the amino crown ether and the amino-modified lithium ion sieve, the lithium adsorption material has a high adsorption capacity for lithium ions in the solution and a strong magnesium-lithium selectivity.

[0212] Figure 1 This is a scanning electron microscope image of the lithium adsorption material of Example 1. It can be seen that the lithium ion sieve is evenly distributed in the skeleton and the material structure is loose. Figure 2 This is a scanning electron microscope image of the lithium adsorption material prepared in Comparative Example 4. It can be seen that the structure of the lithium adsorption material is densely packed and irregular.

[0213] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.

Claims

1. A lithium adsorption material, characterized in that The lithium adsorption material includes a polysulfonamide skeleton and an amino-modified lithium ion sieve bonded to the skeleton; The lithium ion sieve is connected to the framework via the structure shown in Formula I; Formula I; The polysulfonamide skeleton includes structural unit A, structural unit B and structural unit C; The structure shown in formula II is formed between the structural unit A and the structural unit C; Formula II; The structure shown in formula III is formed between the structural unit B and the structural unit C; Formula III; Ar1 is a residue of a polyamine; Ar2 is a residue of a polysulfonyl chloride; and Ar3 is a residue of an amino crown ether.

2. The lithium adsorption material according to claim 1, wherein The polyamine is selected from at least one of diethylenetriamine, tetraethylenepentamine, polyethylenepolyamine, polyethyleneimine and polyetheramine; and / or, the polysulfonyl chloride is at least one selected from 1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 1,4-benzenedisulfonyl chloride, 2,4-disulfonyl chloride-mesitylene, biphenyl-4,4'-disulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 2,6-naphthalenedisulfonyl chloride, 1,3-naphthalenedisulfonyl chloride, 2,7-naphthalenedisulfonyl chloride, 1,3,5-benzenetrisulfonyl chloride and 1,3,6-naphthalenetrisulfonyl chloride; And / or, the amino crown ether is selected from at least one of diaminodibenzo-14-crown-4, 1-aza-12-crown-4, N,N'-bis(methoxymethyl)dithioazapurine-12-crown-4, 4',4ʺ(5ʺ)-diaminodibenzo-15-crown-5 ether, diaminodibenzo-15-crown-5 ether, 2-aminomethyl-15-crown-5 and 4'-aminobenzo-18-crown-6.

3. The lithium adsorption material according to claim 1 or 2, wherein The polyamine is polyethyleneimine and / or triethylenetetramine; and / or, the polysulfonyl chloride is 1,3-benzenedisulfonyl chloride and / or 1,2-benzenedisulfonyl chloride; And / or, the amino crown ether is diaminodibenzo-14-crown-4 and / or 2-aminomethyl-15-crown-5.

4. The lithium adsorption material according to claim 2, wherein The weight average molecular weight of the polyethyleneimine or polyetheramine is 80,000-120,000 g / mol.

5. The lithium adsorption material according to claim 1 or 2, wherein Based on the total weight of the lithium adsorption material, the content of the amino-modified lithium ion sieve is 10wt%-35wt%, the content of the structural unit A is 11wt%-30wt%, the content of the structural unit B is 4wt%-10wt%, and the content of the structural unit C is 30wt%-70wt%.

6. The lithium adsorption material according to claim 5, wherein Based on the total weight of the lithium adsorption material, the content of the amino-modified lithium ion sieve is 19wt%-26wt%, the content of the structural unit A is 12wt%-20wt%, the content of the structural unit B is 4wt%-7wt%, and the content of the structural unit C is 50wt%-60wt%.

7. The lithium adsorption material according to claim 1 or 2, wherein The amino-modified lithium ion sieve is a lithium ion sieve modified with an aminosilane coupling agent.

8. The lithium adsorption material according to claim 7, wherein Based on the weight of the amino-modified lithium ion sieve, the content of the aminosilane coupling agent is 0.1 wt %-2 wt %.

9. The lithium adsorption material according to claim 8, wherein The aminosilane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane.

10. The lithium adsorption material according to claim 1 or 2, wherein The lithium ion sieve is selected from titanium-based lithium ion sieves and / or manganese-based lithium ion sieves.

11. The lithium adsorption material according to claim 10, wherein The lithium ion screening 1.33 Mn 1.67 O4, Li2TiO3, LiTi2O4 and Li4Ti5O 12 At least one of; And / or, the average particle size of the lithium ion sieve is 0.01-500 μm.

12. The lithium adsorption material according to claim 11, wherein The average particle size of the lithium ion sieve is 0.03-300 μm.

13. The lithium adsorption material according to claim 1 or 2, wherein The specific surface area of ​​the lithium adsorption material is 8-50m 2 / g; and / or, the pore size of the lithium adsorption material is 0.1-8 μm; And / or, the pore volume of the lithium adsorption material is 15-50 m 3 / g; And / or, the average particle size of the lithium adsorption material is 0.8-3 mm.

14. The lithium adsorption material according to claim 13, wherein The specific surface area of ​​the lithium adsorption material is 25-35 m 2 / g; and / or, the pore size of the lithium adsorption material is 2-4 μm; And / or, the pore volume of the lithium adsorption material is 30-35 m 3 / g; And / or, the average particle size of the lithium adsorption material is 1-1.5 mm.

15. A lithium adsorption material and a preparation method thereof, comprising the following steps: (1) Amino-modifying the lithium ion sieve to obtain an amino-modified lithium ion sieve; (2) uniformly mixing the amino-modified lithium ion sieve, polyamine and amino crown ether in water to obtain a mixed solution 1; (3) Under stirring conditions, an organic solution containing polysulfonyl chloride is dropped into the mixed solution 1 to obtain a mixed solution 2 for reaction, and the reaction product is heat-treated to obtain a semi-solidified cross-linked product, which is then extruded to obtain a lithium adsorption material.

16. The preparation method according to claim 15, wherein In step (1), the lithium ions are screened from titanium-based lithium ion sieves and / or manganese-based lithium ion sieves; and / or, the average particle size of the lithium ion sieve is 0.01-500 μm; And / or, aminosilane coupling agent is used to perform amino modification on the lithium ion sieve.

17. The preparation method according to claim 16, wherein The lithium ion screening 1.33 Mn 1.67 O4, Li2TiO3, LiTi2O4 and Li4Ti5O 12 At least one of; and / or, the average particle size of the lithium ion sieve is 0.03-300 μm; And / or, the aminosilane coupling agent is at least one selected from the group consisting of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane; And / or, the mass ratio of the lithium ion sieve to the aminosilane coupling agent is 1:0.5-2; And / or, the conditions for the amination modification include: pH value of 1-3, reaction temperature of 40-95° C., and reaction time of 0.5-12 h.

18. The preparation method according to claim 15 or 16, wherein In step (3), based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether and the polysulfonyl chloride, the content of the amino-modified lithium ion sieve is 10wt%-35wt%, the content of the polyamine is 11wt%-30wt%, the content of the amino crown ether is 4wt%-10wt%, and the content of the polysulfonyl chloride is 30wt%-70wt%; and / or, the polyamine is at least one selected from diethylenetriamine, tetraethylenepentamine, polyethylenepolyamine, polyethyleneimine and polyetheramine; and / or, the weight average molecular weight of the polyethyleneimine or polyetheramine is 80,000-120,000 g / mol; And / or, the amino crown ether is selected from at least one of diaminodibenzo-14-crown-4, 1-aza-12-crown-4, N,N'-bis(methoxymethyl)dithioazapurine-12-crown-4, 4',4ʺ(5ʺ)-diaminodibenzo-15-crown-5 ether, diaminodibenzo-15-crown-5 ether, 2-aminomethyl-15-crown-5 and 4'-aminobenzo-18-crown-6.

19. The preparation method according to claim 18, wherein Based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether and the polysulfonyl chloride, the content of the amino-modified lithium ion sieve is 19wt%-26wt%, the content of the polyamine is 12wt%-20wt%, the content of the amino crown ether is 4wt%-7wt%, and the content of the polysulfonyl chloride is 50wt%-60wt%; and / or, the polyamine is polyethyleneimine and / or triethylenetetramine; And / or, the amino crown ether is diaminodibenzo-14-crown-4 and / or 2-aminomethyl-15-crown-5.

20. The preparation method according to claim 15 or 16, wherein In step (3), the content of the polysulfonyl chloride in the organic solution containing polysulfonyl chloride is 0.25 wt%-10 wt%; and / or, the polysulfonyl chloride is at least one selected from 1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 1,4-benzenedisulfonyl chloride, 2,4-disulfonyl chloride-mesitylene, biphenyl-4,4'-disulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 2,6-naphthalenedisulfonyl chloride, 1,3-naphthalenedisulfonyl chloride, 2,7-naphthalenedisulfonyl chloride, 1,3,5-benzenetrisulfonyl chloride and 1,3,6-naphthalenetrisulfonyl chloride; And / or, the reaction conditions include: reaction temperature of 10-70°C; reaction time of 5-300 min; And / or, the heat treatment conditions include: heat treatment temperature of 80-150° C.; heat treatment time of 5-60 min.

21. The preparation method according to claim 20, wherein In step (3), the content of the polysulfonyl chloride in the organic solution containing polysulfonyl chloride is 0.5 wt%-5 wt%; and / or, the polysulfonyl chloride is 1,3-benzenedisulfonyl chloride and / or 1,2-benzenedisulfonyl chloride; And / or, the reaction conditions include: reaction temperature of 30-50°C; reaction time of 10-60 min; And / or, the heat treatment conditions include: heat treatment temperature of 90-120° C.; heat treatment time of 10-30 min.

22. The preparation method according to claim 15 or 16, wherein The preparation method further comprises: eluting the lithium adsorption material with an acidic solution.

23. The preparation method according to claim 22, wherein The acidic solution is selected from hydrochloric acid and / or sulfuric acid; and / or, the concentration of the acidic solution is 0.01-1 mol / L; And / or, the elution time is 0.5-24h.

24. A lithium adsorption material obtained by the preparation method according to any one of claims 15 to 23.

25. Use of the lithium adsorption material according to any one of claims 1 to 14 and 24 in extracting lithium from salt lakes.

26. The use according to claim 25, wherein: The magnesium-lithium ratio of the salt lake is 10-500:

1.

27. The use according to claim 25 or 26, wherein: The ratio of the mass concentration of sulfate ions to the mass concentration of lithium ions in the salt lake is 200-700:1.

Citation Information

Patent Citations

  • Preparation method and application of sulfonic-acid type anionic nano adsorbent

    CN109351346A

  • Acid-resistant composite membrane as well as preparation method and application thereof

    CN114432903A